Influence of wearing a face mask on speech properties - Aharonson Vered; Carlson Craig S.; Postema Michiel; Putter-Katz Hanna; Tetin Schneider Simona (Current Directions in Biomedical Engineering)
The increased use of face masks for infection prevention has resulted in difficulties in speech understanding. Thus, there is a need for tuning of acoustic plans in hearing aids to compensate for the loss of acoustic information due to the mask.Previous studies focused on isolated vowel sounds. Our study measured the effect of surgery masks on the acoustic attributes of vowels and compared the effect of isolated to co-articulated vowels. The voices of 45 male speakers were recorded whilst pronouncing isolated vowels and vowels within the co-articulation in a sentence. All recordings were repeated with the participants wearing a surgical mask. Acoustic factors of length, intensity, pitch, formants, shimmer, and jitter were extracted from the vowels in all the different conditions. The differences between masked and unmasked acoustics in the co-articulated vowels were found to be smaller than the isolated vowels acoustic features. These preliminary results improve the quantification of the effect of hearing a face mask in the real-life production of speech.